Fenofibrate mediated activation of PPARα negatively regulates trophoblast invasion. (August 2022) - Singh, Sunil; Dhar, Ruby; Karmakar, Subhradip
Abstract: The Peroxisome Proliferator-Activated Receptor-alpha (PPARα) is a member of the ligand-dependent nuclear receptor superfamily known for their crucial role in lipid metabolism. The expression and role of PPARα in trophoblast cells are not very well known. Trophoblast invasion is one of the most critical processes required for successful implantation of the developing embryo into the maternal endometrium. Defects in this process are associated with adverse pregnancy outcomes such as FGR(Fetal Growth Restriction), Preeclampsia, and choriocarcinoma. In this present study, we investigated the role of the ligand-activated transcription factor, Peroxisome proliferator-activated receptor (PPARα) in regulating trophoblast cell invasion using cell lines and explants-based models. Immunohistological localization of PPARα in human placental tissues showed a gestational variation with relatively low expression at term as compared to early trimester. PCR and Western Blot also confirmed this. Further to delineate the effect of PPAR alpha on trophoblast invasion, EVT derived HTR8/SVneo cell lines were stimulated with PPARα agonist, i.e., fenofibrate (FF). Fenofibrate stimulation led to an increased activation and nuclear translocation of PPARα, followed by reduced migration and invasion of these cells in a matrigel invasion assay (Boyden chamber). PPAR alpha stimulation also led to a reduced MMP-2/9 expression following our previous observation. Thus, we may conclude that PPARα to be playing a very important regulatory role in orchestrating the invasive trophoblast programme and hence it seems plausible for it to be associated with PE, which is often characterized by a shallow trophoblast invasion. Highlights: Fetal and maternal derived factors tempo-spatially regulate trophoblast invasion. Appropriate regulation of Trophoblast invasion is vital for the successful maintenance of pregnancy. PPARα negatively regulates trophoblast invasion through inhibition of MMPs.